Electrospun polyimide/organic montmorillonite composite nanofibrous membranes with enhanced mechanical properties and flame retardancy. (February 2020) - Wang, Liang; Cui, Lingyan; Fan, Jie; Liu, Yong
Polyimide/organic montmorillonite nanofibrous membranes were fabricated through electrospinning of polyamic acid/organic montmorillonite precursors followed by a thermal imidization process. Scanning electron microscopy micrographs showed small amounts of organic montmorillonite addition (<3%) and increase in the diameter of polyimide nanofibers. However, higher organic montmorillonite fraction generated microspheres due to the aggregation of clay nanoplatelets. Transmission electron microscopy images indicated that both exfoliated and intercalated organic montmorillonites existed in polyimide nanofibers when low quantity of clay was loaded (<3%). As the clay amount increased, exfoliated structure disappeared and stacked clay layers were observed. The optimum concentration of organic montmorillonite is 3%. By incorporating 3% clay, the tensile strength and modulus of membrane increased by 92.1 and 48.6%, respectively. Moreover, the limiting oxygen index value arose from 29.2 to 30.4%. Higher thermal stability was also achieved because of the heat barrier effect of clay layers. The onset decomposition temperature increased by 17℃ by adding 5% clay. These results demonstrate that tiny organic montmorillonite incorporation is relatively effective for improving the mechanical properties as well as flame retardancy of polyimide nanofibrous membrane.